Pathogenesis and comprehensive treatment strategies of sarcopenia in elderly patients with type 2 diabetes mellitus - Hou, Yang; Xiang, Jia; Wang, Bo; Duan, Shoufeng; Song, Rouxuan; Zhou, Wenhu; Tan, Songwen; He, Binsheng (Frontiers in Endocrinology, 2024)
Sarcopenia and diabetes are two age-related diseases that are common in the elderly population, and have a serious effect on their general health and quality of life. Sarcopenia refers to the progressive loss of muscle mass, strength and function, whereas diabetes is a chronic disease characterized by elevated blood sugar levels. The comorbidity of sarcopenia and diabetes is particularly concerning, as people with diabetes have a higher risk of developing sarcopenia due to the combination of insulin resistance, chronic inflammation and reduced physical activity. In contrast, sarcopenia destroyed blood sugar control and exacerbated the development of people with diabetes, leading to the occurrence of a variety of complications. Fortunately, there are a number of effective treatment strategies for sarcopenia in people with diabetes. Physical exercise and a balanced diet with enough protein and nutrients have been proved to enhance the muscular quality and strength of this population. Additionally, pharmacological therapies and lifestyle changes can optimize blood sugar control, which can prevent further muscle loss and improve overall health outcomes. This review aims to summarize the pathogenesis and comprehensive treatment strategies of sarcopenia in elderly patients with type 2 diabetes, which help healthcare professionals recognize their intimate connection and provide a new vision for the treatment of diabetes and its complications in this population. Through early identification and comprehensive treatment, it is possible to improve the muscle function and general quality of life of elderly with diabetes and sarcopenia.